(untitled) (Research, Society and Development, 2020)
From the perspective of rain drainage, urbanization is commonly accompanied by the rapid increase in impermeable areas, resulting in changes in the hydrological and hydraulic characteristics of a watershed. Among the main effects of these changes can be mentioned the increase in the flow speed, the increase of the damages resulting from floods and the possibility of pollution of the water bodies by the carrying of substances. Thus, this study aimed to analyze the spatio-temporal evolution of scientific works published and indexed in the Web of Science database regarding the relationship between urban drainage and sanitation. A scientometric survey was conducted that resulted in a sample of 34 articles, analyzed using descriptive statistics and content analysis. The results obtained indicate an increase in the number of articles published between 1994 and 2019, with Brazil corresponding to the country with the largest number of publications (n = 14). Regarding the areas of knowledge, it was noted that those with the largest number of articles correspond to Water Resources (18%), Environmental Sciences and Ecology (17%) and Engineering (12%). The keywords most cited in the articles were “sustainability”, “urban drainage”, “management”, “systems”, “sanitation”, “water”, “cities”, “climate change”, “health” and “pollution”. It highlights the importance of multidisciplinary research involving new approaches to rainwater management seeking to build more sustainable cities.